Caracterização de biocarvões de palha de café e casca de eucalipto produzidas a 350 e 600ºC - Barbosa, Cristiane Francisca (2016)
Biochar is a product of the thermal decomposition of organic materials in low oxygen concentration and controlled temperatures. The agronomic and environmental benefits of its use are associated with the pyrolysis temperature and raw material